Persistent effect of salt reduction in schoolchildren and their families: 1-year follow-up after an application-based cluster randomized controlled trial - Yuan Li; Puhong Zhang; Feng J. He; Rong Luo; Jing Song; Changqiong Wang; Fengge Chen; Wei Zhao; Yuhong Zhao; Hang Chen; Tianyong Wu; Xiaoyan Wang; et al. (BMC Medicine)
Abstract Background A 12-month cluster randomized controlled trial (RCT) demonstrated the effectiveness of an application-based education program in reducing the salt intake and systolic blood pressure (SBP) of schoolchildren’s adult family members. This study aimed to assess whether the effect at 12 months persisted at 24 months. Methods Fifty-four schools were randomly assigned to either the intervention or control group. All participants (594 children in grade 3 and 1188 of their adult family members) who completed the baseline survey were contacted again 12 months after the trial. The primary outcome was the difference in salt intake change between the intervention and control groups at 24 months versus baseline and 12 months, measured by the mean two consecutive 24-h urinary sodium excretions. The secondary outcome was the difference in the change of blood pressure and salt-related Knowledge, Attitude, Practice (KAP) score. Results The difference in salt intake change in adults between the intervention and control groups after adjusting for confounding factors was − 0.38 g/day at 24 months versus baseline (95% CI − 0.81 to 0.05, p = 0.09), following the − 0.83 g/day (95% CI − 1.25 to − 0.41, p < 0.001) at 12 months. The adjusted difference in SBP change was − 2.19 mm Hg (95% CI − 3.63 to − 0.76, p = 0.003) at 24 months versus baseline, following the − 1.80 mm Hg (95% CI − 3.19 to − 0.40, p = 0.01) at 12 months. The intervention group had a higher KAP score than the control group both at 12 months and at 24 months versus baseline. No significant changes were found in children. Conclusions The effect of the education program on adults’ salt intake faded, but the SBP lowering effect and the improvement of KAP score remained 12 months after the completion of the RCT. Continuous efforts are needed to maintain the salt reduction effects in real-world settings. Trial registration ChiCTR1800017553. Registered on August 3, 2018.